201k views
1 vote
Which expression is equivalent to

2/3(9x-6)+4(1/2 x -- 1/2)


1/2 and 3/4 are fractions

1 Answer

3 votes

Answer:

Given expression
(2)/(3)(9x-6)+4((1)/(2)x-(1)/(2)) is equivalent to the expression
2(4x-3).

Explanation:

Given expression is
(2)/(3)(9x-6)+4((1)/(2)x-(1)/(2))

To simplify the expression:


(2)/(3)(9x-6)+4((1)/(2)x-(1)/(2))=(18x-12)/(3)+(4x-4)/(2)

Taking LCM 6 to the above expression we get


=((18x-12)2+3(4x-4))/(6) (Applying multiplication rules)


=(36x-24+12x-12)/(6) ( doing sums to the terms)


=(48x-36)/(6)


=8x-6

We can take common number 2 outside to the above expression


=2(4x-3)

Therefore
(2)/(3)(9x-6)+4((1)/(2)x-(1)/(2))=2(4x-3)

Therefore given expression
(2)/(3)(9x-6)+4((1)/(2)x-(1)/(2)) is equivalent to the expression
2(4x-3).

User Marxjohnson
by
5.7k points